Efektifitas Pengimplementasian UNPoA dalam Mengatasi Masalah Penyelundupan Senjata di Jalur Perbatasan Indonesia-Filipina Selatan - Mufti Hatur Rahma; Agussalim Burhanuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
The illicit circulation of small arms and light weapons along the southern border between Indonesia and the Philippines presents a critical challenge to both national and regional stability. The remote and difficult-to-access terrain, coupled with the frequent movement of non-state armed actors, contributes significantly to the deteriorating security landscape. This paper explores how effectively Indonesia and the Philippines have implemented the United Nations Programme of Action (UNPoA) in their efforts to combat this issue. Using a qualitative approach through literature review and guided by the international regime theory, this analysis highlights the current limitations in addressing the problem. Despite formal commitments by both governments through ratification and periodic reporting under the UNPoA, the actual enforcement on the ground remains inadequate. Key obstacles include poor coordination among domestic agencies, insufficient operational resources, and a lack of robust cross-border collaboration. This study emphasizes the necessity for continuous adaptation and local contextualization of international frameworks to ensure they can be realistically and effectively applied in areas with unique challenges.